Functional Mapping of AGO-Associated Zika Virus-Derived Small Interfering RNAs in Neural Stem Cells - Zeng, Jianxiong; Luo, Zhifei; Dong, Shupeng; Xie, Xiaochun; Liang, Xinyan; Yan, Youzhen; Liang, Qiming; Zhao, Zhen (Frontiers in Cellular and Infection Microbiology, 2021)
Viral interfering RNA (viRNA) has been identified from several viral genomes via directly deep RNA sequencing of the virus-infected cells, including zika virus (ZIKV). Once produced by endoribonuclease Dicer, viRNAs are loaded onto the Argonaute (AGO) family proteins of the RNA-induced silencing complexes (RISCs) to pair with their RNA targets and initiate the cleavage of target genes. However, the identities of functional ZIKV viRNAs and their viral RNA targets remain largely unknown. Our recent study has shown that ZIKV capsid protein interacted with Dicer and antagonized its endoribonuclease activity, which requires its histidine residue at the 41st amino acid. Accordingly, the engineered ZIKV-H41R loss-of-function (LOF) mutant virus no longer suppresses Dicer enzymatic activity nor inhibits miRNA biogenesis in NSCs. By combining AGO-associated RNA sequencing, deep sequencing analysis in ZIKV-infected human neural stem cells (NSCs), and miRanda target scanning, we defined 29 ZIKV derived viRNA profiles in NSCs, and established a complex interaction network between the viRNAs and their viral targets. More importantly, we found that viRNA production from the ZIKV mRNA is dependent on Dicer function and is a limiting factor for ZIKV virulence in NSCs. As a result, much higher levels of viRNAs generated from the ZIKV-H41R virus-infected NSCs. Therefore, our mapping of viRNAs to their RNA targets paves a way to further investigate how viRNAs play the role in anti-viral mechanisms, and perhaps other unknown biological functions.